First Contact Access Evaluated by PCATOOL professional version in a pre-pandemic setting by COVID-19 from Alfenas, Sul de Minas Gerais (Research, Society and Development, 2023)
The Family Health Strategy (FHS) is indispensable for the Unified Health System (SUS), as it improves the guidelines for primary care and expands its resolutivity. Therefore, the questionnaire PCATool Professionals version is an essential instrument to measure the First Contact Access - Accessibility. This question, when it has adequate use and accessibility and acts in a timely manner, makes primary care the gateway to other levels of health care. Thus, the objective of this research is the diagnostic evaluation of primary health care in the ESF network of Alfenas, Minas Gerais, from the application of the questionnaire PCATool-Brazil Professionals Version. Approved by the ethics committee with number 814.099, the research was carried out through the application, in printed form, of the questionnaire PCAtool-Brazil Professionals Version to 117 employees of the ESF of the city. The data collected were organized in a table in Excel software and, later, the scores were calculated following the PCAtool-Brazil Manual Professional Version, being the mean the main measure of data definition. With this, the quality of first contact access was measured and negative results (